Uniformed Services and the Field Hospital Experience During Coronovirus Disease 2019 (SARS-CoV-2) Pandemic: Open to Closure in 30 Days With 1, 100 Patients: The Javits New York Medical Station. Issue 5 (19th January 2022) - Brady, Kevin; Milzman, Dave; Walton, Edward; Sommer, Darren; Neustadtl, Alan; Napoli, Anthony
ABSTRACT: Introduction: The surge of SARS-CoV-2-virus infected (COVID-19) patients presenting to New York City (NYC) hospitals quickly overwhelmed and outnumbered the available acute care and intensive care resources in NYC in early March 2020. Upon the arrival of military medical assets to the Javits Convention Center in NYC, the planned mission to care for non-SARS-CoV-2 patients was immediately changed to manage patients with (SARS-CoV-2)COVID-19 and their comorbid conditions. Healthcare professionals from every branch of the uniformed services, augmented by state and local resources, staffed the Javits New York Medical Station (JNYMS) from April 2020. Methods: The data review reported aggregated summary statistics and participant observations collected by N.Y. State and U.S. military officials. Results: During the 28 days of patient intake at the JNYMS, 1, 095 SARS-CoV-2-positive patients were transferred from NYC hospitals to the JNYMS. At its peak, the JNYMS accepted 119 patients in a single day, had a maximum census of 453, and had a peak intensive care unit census of 35. The median length of stay was 4.6 days (interquartile range: 3.1-6.9 days). A total of 103 patients were transferred back to local hospitals, and there were 6 deaths, with an overall mortality rate of 0.6% (95% CI, 0.3-1.2). Discussion and Conclusions: This is the first report of the care provided at the JNYMS. Within 2 weeks, this multi-agency effort was able to mobilize to care for over 1, 000 SARS-CoV-2 patients with varying degrees of illness in a 1-month period. This was the largest field hospital mobilization in the U.S. medical history in response to a non-wartime pandemic. Its success with huge patient throughput including disposition and low mortality relieved critical overcrowding and supply deficiencies throughout NYC hospitals. The downstream impact likely saved additional hundreds of lives and reduced stress on the system during this healthcare crisis.